PENGARUH TERAPI MUSIK DZIKIR TERHADAP TINGKAT DEPRESI PADA LANSIA DI RT 3 RW 2 RUMAH DINAS TNI-AL PULUNGAN - Umamah, Farida Umamah; Fabiyanti, Annisa (Unusa Press, 2018)
The effects of aging process experienced by the elderly cause various physical, mental, and socio-economic problems. One of the psychological problems experienced by them is depression. Hence, this study was purposed to find out the effect of dhikr music therapy on the depression level in the elderly living in the naval official housing complex RT 3 RW 2 Pulungan. This pre-experimental study was done by using a one-group pretest-posttest design, involving the population totaling 30 people. 28 elderly people aged 60-74 years were taken as the samples by using probability sampling, namely simple random sampling technique. The independent variable was the dhikr music therapy, whereas the  dependent variable was the depression level in the elderly. The instrument used in this study was DASS 42 (Depression Anxiety Stress Scale) implemented to the elderly, then analyzed by using Wilcoxon signed-rank test. The result of this study showed that of 28 respondents before receiving dhikr music therapy, most of them (57.1%) had severe depression After receiving the therapy, half of them (50.0%) had mild depression. The result of analysis showed that ρ = 0.000 in which ρ< 0.05 so that H0 was rejected. It illustrated that there was an effect of dhikr music therapy on the depression level in the elderly living in the naval official housing complex RT 3 RW 2 Pulungan.  In conclusion, dhikr music therapy is effective to decrease the level of depression experienced by the elderly. Therefore, the nurses are expected to continue the activity of dhikr music therapy in the above-mentioned location of this study so that the elderly people get a motivation to do it routinely in group.